The Influence of Usability and User Experience of the RRI Digital Application on Continuous Usage with User Satisfaction as a Mediating Variable - Tamara Pratiwi; Nurjanah Nurjanah; Rumyeni Rumyeni (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research focuses on analyzing the influence of usability and user experience of the RRI Digital application on continuous usage, with user satisfaction as a mediating variable. The rapid digital transformation has driven conventional media, including radio, to adapt in order to remain relevant amidst changes in public information consumption behavior. As a public broadcasting institution, RRI launched the RRI Digital application to provide easier access to broadcasts and multimedia content. However, the sustainability of application usage greatly depends on the quality of user interaction. The theoretical framework applied in this study is the Technology Acceptance Model (TAM) and the Expectation-Confirmation Model (ECM), which explain the roles of perceived ease of use, usefulness, and satisfaction in shaping the intention of continuous usage. The research method employed is quantitative, using Structural Equation Modeling (SEM-PLS), involving respondents who are RRI Digital users in Pekanbaru. The research sample consisted of 321 respondents. The analysis was carried out using SEM based on Partial Least Squares (PLS), an appropriate method to test relationships among variables with mediation complexity. The findings indicate that usability and user experience have a positive and significant effect on user satisfaction. Furthermore, satisfaction was proven to be a mediating variable that strengthens the relationship between usability, user experience, and continuous usage. These results provide strategic recommendations for RRI Digital to remain competitive with other entertainment and information platforms that are increasingly growing. This research highlights the importance of usability and user experience in enhancing user satisfaction and loyalty toward the RRI Digital application. Application developers are advised to focus on user-friendly design and enjoyable interactive experiences to encourage continuous usage among users.